Music, politics, cultural revival: the dialogics of songs at Biras/ Galas in post-independence Zimbabwe. - Viriri, Advice (MSU Press, 2016)
The article does not only showcase the dominance of Pungwe as a historical theatrical narrative of Chimurenga which legitimises the liberation war theme in the post-independence Zimbabwean politics but it further demonstrates that music, as a trenchant political site in Africa, has become a major spot for thinking through politics. It assesses Pungwe's attempt to reconstruct the liberation war history embedded in the evocation of a past through the enactment of Chimurenga War as a crucial tool for the articulation, crystalisation and contestation of power. Biras/ Galas as Pungwe manifest an engagement of Zimbabwean political circumstances in search for a breakthrough, through music, as the most widely appreciated art form. This occupies a form of time zone (trauma time) better understood through the role that music plays in rehabilitation situations, marking the continuance of a new nation. The article further examines elements of anticipatory-driven performance experience where the audience engages in interactions at biras/galas with expected mainstream collective Zimbabwean memory. This responds to serious needs, especially of the ‘decade of crisis’ to protect Pungwe as part of African cultural diversity whose traditional values specifically, modes of healing help to safeguard and promote this intangible cultural heritage. The article will show how this new form of Pungwe through its multi-medial quality, becomes a new way of handling traditional healing processes. Chimurenga War songs, coupled with music compositions of this ‘decade of crisis’ are often associated with creativity and high art, which this article seeks to find out whether its content is always multi-parametric.polyphonic and an ensemble of coded voices of the struggle whose cogency lies in Bakhtin’s general principal and ideas of polyphony and dialogism in language which will be explored as ways of organising our post-independence thinking. The article will show that language has been traditionally considered as an already established, self-contained system of linguistic communication that sets out rules of socio-political conventions that people make use of in expressing themselves even through music.